Gendered access and control of irrigation and its implications for meeting the MDGs in Zimbabwe AAG Conference, New York 24-28 February 2012 - Mapedza, Everisto D. (2012)
Gender is central in understanding irrigation systems within the developing world. The different roles and responsibilities that society ascribes to both men, women, children and the different age groups will impact on their ability to participate and benefit from irrigation investments. Irrigation is often perceived as a mechanism for improving the livelihoods of the rural farmers and helps meet the United Nations Millennium Development Goals (MDGs) in sub-Saharan Africa of which Zimbabwe is part of. It is, however, important to understand that benefits from irrigation are gendered. This study assesses the intersection of gender, politics, power dynamics and how these play out and result in differential outcomes in irrigation landscapes of Zimbabwe. The major findings were that for successful poverty alleviation through irrigation investments, it is important to understand under which circumstances irrigation investments are benefiting poor women, men and children. The research also found out that increased economic crisis, rural-urban migration and high incidences of HIV/AIDS have all resulted in women providing the bulk of labour in the scheme in the face of extension approaches which are biased towards 'male farmers.' This study has important policy implications in that understanding of gender is important in order to improve rural livelihoods through investments such as irrigation.